Boundaries and limitations of human rights: A contribution to the discussion - Biłgorajski, Artur (Scientific Journal of Bielsko-Biala School of Finance and Law, 2023)
The study is devoted to the analysis and evaluation of principal mechanisms for limiting human rights, namely: exceptions by definition, the concept of abuse of rights, limitation clauses of general or specific nature and derogation clauses. The author puts forward the thesis that the recognition of a possibility of introducing restrictions on human rights by way of exception does not nullify the principle of full and effective enjoyment of human rights, but rather clarifies it, permitting to resolve conflicts not only between individual interests and goods, but also of individual rights and interests with collective ones. Obviously, this study does not aspire to be exhaustive. Its purpose is only to outline the topic and the problems involved